Recent infection as a risk factor for cerebrovascular ischemia - Grau, Armin J.; Buggle, Florian; Heindl, Silke; Steichen-Wiehn, Christianne; Banerjee, Tomas; Maiwald, Matthias; Rohlfs, Marion; Suhr, Helge; Fiehn, Walter; Becher, Heiko; Hacke, Werner (Stroke, 1995)
Background and Purpose Previous infection is discussed as a risk factor for ischemic stroke in children and younger adults. We tested the hypothesis that the role of recent infection in cerebrovascular ischemia is not restricted to younger patients and investigated which infections are mainly relevant in this respect. - Methods We performed a case-control study with 197 patients aged 18 to 80 years with acute cerebrovascular ischemia and 197 randomly selected control subjects matched for sex, age, and area of residence. - Results Infection within 1 week before ictus or examination was significantly more common among patients (38 of 197) than control subjects (10 of 197; odds ratio [OR], 4.5; 95% confidence interval [CI], 2.1 to 9.7). Patients more often had febrile and subfebrile infections (≥37.5°C) than control subjects (29 of 197 versus 5 of 197; OR, 7.0; 95% CI, 2.5 to 20). Respiratory tract infections were most common in both groups. Bacterial infections dominated among patients but not among control subjects. Infection increased the risk for cerebrovascular ischemia in all age groups; this reached significance for patients aged 51 to 60 and 61 to 70 years. The profile of vascular risk factors was similar in patients with and patients without previous infection. Infection remained a significant risk factor when previous stroke, hypertension, diabetes mellitus, coronary heart disease, and current smoking were included as covariates in a logistic model (OR, 4.6; 95% CI, 1.9 to 11.3). - Conclusions Recent infection, primarily of bacterial origin, may be a risk factor for cerebrovascular ischemia in older as well as younger patients.